Inside Cover: A Nanoarchitecture Based on Silver and Copper Oxide with an Exceptional Response in the Chlorine‐Promoted Epoxidation of Ethylene (Angew. Chem. Int. Ed. 37/2016). Issue 37 (28th July 2016) - Ramirez, Adrian; Hueso, Jose L.; Suarez, Hugo; Mallada, Reyes; Ibarra, Alfonso; Irusta, Silvia; Santamaria, Jesus
Abstract : When silver meets copper oxide : A material composed of silver nanostructures (represented by the islands) dispersed within a copper oxide support (the sea) was found to be an excellent catalyst for the selective epoxidation of ethylene at temperatures below 250 °C. As reported by J. L. Hueso, J. Santamaria et al. in their Communication onpage 11158 ff., the catalyst can accommodate chlorine promotors in a single pretreatment step, with the CuO acting as a Cl sponge, thus avoiding, for the most part, irreversible catalyst poisoning.